2019
DOI: 10.1093/ckj/sfz117
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the accuracy of ICD-10 coding for measuring rates of and mortality from acute kidney injury and the impact of electronic alerts: an observational cohort study

Abstract: Background The application of a uniform definition for acute kidney injury (AKI) is vital to advance understanding and management of AKI. International Classification of Diseases (Tenth Revision) (ICD-10) coding is frequently used to define AKI, but its accuracy is unclear. The aim of this study was to determine whether ICD-10 coding is a reliable method of monitoring rates and outcomes of AKI in inpatients compared with biochemically defined AKI, and whether electronic alerts (e-alerts) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…They did not use a biochemical definition for AKI and relied instead on clinical coding, which can lead to significant underascertainment. 29 In addition, a meta-analysis by James et al 30 showed the hazards ratios for AKI were higher in participants with diabetes compared with those without diabetes at any level of eGFR. Once again, the definition for AKI relied on administrative codes in these studies, thereby underestimating milder forms of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…They did not use a biochemical definition for AKI and relied instead on clinical coding, which can lead to significant underascertainment. 29 In addition, a meta-analysis by James et al 30 showed the hazards ratios for AKI were higher in participants with diabetes compared with those without diabetes at any level of eGFR. Once again, the definition for AKI relied on administrative codes in these studies, thereby underestimating milder forms of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a common and devastating pathologic condition in part due its higher incidence in the elderly and its association with an increased short- and long-term mortality ( Levey and James, 2017 ; Hounkpatin et al, 2019 ; Martin-Cleary et al, 2019 ; Logan et al, 2020 ). Moreover, AKI is closely related to chronic kidney disease (CKD) as AKI may accelerate CKD progression to end-stage renal disease (ESRD) and CKD predisposes to AKI ( Venkatachalam et al, 2015 ; Siew et al, 2016 ; Ruiz-Ortega et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that different definitions of AKI would affect the number of AKI cases and utilization rate of dialysis-requiring AKI. Several studies have showed inadequate validity and accuracy of using ICD discharge coding to identify AKI 22 – 25 . Despite SCr-based defined AKI is a relatively new concept to allow early identification and prevention of patients at risk for AKI, we found ICD-9 discharge coding for AKI were sensitive to hospitalized patients with more severe stage of SCr-based defined AKI 23 .…”
Section: Discussionmentioning
confidence: 99%